Stress-Modulated Pathways - Rohleder, Nicolas (2021)
Stress is a condition or an experience that is pervasive throughout human life. While there are many definitions of stress, a common notion is that stress is processed in the central nervous system and has effects on health that are mediated by stress-modulated pathways. Several brain areas, such as the amygdala and the broader limbic system, are involved in interpreting situations as potentially stressful. The signals of these areas converge in the hypothalamus, which orchestrates peripheral stress-modulated pathways, mainly the hypothalamus-pituitary-adrenal (HPA) axis and the autonomic nervous system (ANS). Health effects of stress are mediated by long-term alterations of basic stress system activity, which has downstream effects on pathophysiological pathways such as the inflammatory system.<br
Keywords: stress; HPA axis; autonomic nervous system; inflammation; C-reactive protein; Interleukin-6; neuroendocrine and autonomic systems